2021
DOI: 10.3389/fcell.2021.697832
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism of Cannabidiol in Suppressing Hepatocellular Carcinoma by Inducing GSDME Dependent Pyroptosis

Abstract: Cannabidiol (CBD), a phytochemical derived from Cannabis sativa L., has been demonstrated to exhibit promising anti-tumor properties in multiple cancer types. However, the effects of CBD on hepatocellular carcinoma (HCC) cells remain unknown. We have shown that CBD effectively suppresses HCC cell growth in vivo and in vitro, and induced HCC cell pyroptosis in a caspase-3/GSDME-dependent manner. We further demonstrated that accumulation of integrative stress response (ISR) and mitochondrial stress may contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 59 publications
(75 reference statements)
1
30
0
Order By: Relevance
“…It was previously shown that CBD induced autophagy-dependent cell death [23]. However, other cell death pathways cannot be excluded, e.g., pyroptosis, as shown in primary liver cancer cells in response to CBD [46]. CBD also induced MPT-driven necrosis (mitochondrial permeability transition) in leukemic cells, initiated by severe oxidative stress and Ca 2+ overload [37].…”
Section: Discussionmentioning
confidence: 97%
“…It was previously shown that CBD induced autophagy-dependent cell death [23]. However, other cell death pathways cannot be excluded, e.g., pyroptosis, as shown in primary liver cancer cells in response to CBD [46]. CBD also induced MPT-driven necrosis (mitochondrial permeability transition) in leukemic cells, initiated by severe oxidative stress and Ca 2+ overload [37].…”
Section: Discussionmentioning
confidence: 97%
“…In this study, our result showed that GSDME may play a tumor promoting role in HCC. Though, small molecule drugs such as cannabidiol and miltirone may induce HCC cell death through GSDME-mediated pyroptosis ( Zhang et al, 2020b ; Shangguan et al, 2021 ), non-cleavable or pore-defective GSDME was also proved to be not tumor suppressing ( Zhang et al, 2020a ). The detailed role of GSDME in HCC are worthy of further exploring.…”
Section: Discussionmentioning
confidence: 99%
“…However, owing to the tumor heterogeneity of HCC and the different analysis strategies used in each study, the lncRNA signatures identified are different and it is necessary to develop individualized treatment strategies and improve the precision of prediction ( 4 ). Pyroptosis, a newly recognized type of programmed cell death, may have an inhibitory role in the progression of HCC ( 8 , 34 ). However, the lncRNAs involved in the regulation of pyroptosis and the potential of pyroptosis-related lncRNA signatures to predict prognosis of HCC patients have still remained unclear.…”
Section: Discussionmentioning
confidence: 99%